CLINICOHEMATOLOGICAL, IMMUNOPHENOTYPING, MOLECULAR PROFILE, AND OVERALL SURVIVAL IMPACT IN ACUTE LYMPHOID LEUKEMIA PATIENTS FROM NORTH INDIA: Survival Impact in ALL - MANOJ KUMAR; MOHIT CHOWDHRY; RAJ NATH MAKROO; DEEPIKA RANI; VANDANA SHARMA; PANKAJ SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cytogenetic plays an inevitable role in predicting the diagnosis of acute leukemia. The recurrent chromosomal aberrations in acute leukemia have provided critical insights into the pathophysiological mechanism of leukemogenesis. Cytogenetics findings at diagnostics provide important information for decision-making in both childhood and adult acute lymphoblastic leukemia (ALL). The cure rate for ALL is >80% in children and 35% in adults. Despite the therapeutic advances in ALL, several important biological and pathophysiological questions remain to be answered to achieve an accurate diagnosis, timely prognosis, and maximum therapeutic benefit. Methods: The present study was carried out at tertiary care hospital, New Delhi, India. A total of 144 newly diagnosed ALL patients were analyzed for clinicohematological profile, immunophenotyping, conventional, and molecular cytogenetics. Results: The study population was found to have normal karyotypes in most of the cases; however, abnormalities also reported. Our study clearly indicates that the application of fluorescence in situ hybridization has increased sensitivity and accuracy for detecting various chromosomal abnormalities, more so with the cryptic rearrangements. Conclusion: We observed that the prevalence of the molecular subgroup of leukemia with a potential for a favorable clinical outcome (ETV6-RUNX1 and hyperdiploidy) in precursor B-ALL is higher in the North India.